Clinical findings and outcomes in patients with possible usual interstitial pneumonia. Issue 4 (April 2015) - Lee, Jin Wook; Shehu, Esmeralda; Gjonbrataj, Juarda; Bahn, Young Eun; Rho, Byung Hak; Lee, Mi-Young; Choi, Won-Il
Summary: Background: Patients with possible usual interstitial pneumonia (UIP) constitute a substantial group, and their clinical characteristics and outcomes are not well defined. We compared the clinical characteristics and survival between patients with possible UIP and the UIP pattern. Methods: We evaluated 62 patients with possible UIP and 544 patients with the UIP pattern. Both groups were diagnosed by clinical characteristics and high-resolution computed tomography (HRCT) findings. Two radiologists performed radiological evaluation based on the new idiopathic pulmonary fibrosis (IPF) guidelines. Two risk-stratification methods were used to compare UIP pattern and possible UIP patients. Results: The groups had similar demographic and clinical characteristics. Pulmonary function tests revealed no significant differences in lung volumes between the 2 groups. However, DLCO was significantly lower with the UIP pattern than with possible UIP ( p  = 0.004). Multivariate analysis showed age, sex, and carbon monoxide diffusing capacity (DLCO) as important independent variables for survival. The UIP HRCT pattern did not affect survival (hazard ratio, 0.83; 95% confidence interval, 0.51–1.24; p  = 0.32). Possible UIP was not associated with prognosis when independent predictors for survival rate and propensity score were considered. In the case-control study, the 3-year survival rate was 44.6% in the UIP pattern group and 56.8% in the possible UIP group ( p  = 0.16). Conclusions: Clinical characteristics and outcomes were similar in possible UIP and UIP patients, except for differences in DLCO. The UIP pattern itself did not affect survival.